Use of a safety climate questionnaire in UK health care: factor structure, reliability and usability. Issue 5 (30th October 2006) - Hutchinson, A; Cooper, K L; Dean, J E; McIntosh, A; Patterson, M; Stride, C B; Laurence, B E; Smith, C M
Abstract : Aim: To explore the factor structure, reliability, and potential usefulness of a patient safety climate questionnaire in UK health care. Setting: Four acute hospital trusts and nine primary care trusts in England. Methods: The questionnaire used was the 27 item Teamwork and Safety Climate Survey. Thirty three healthcare staff commented on the wording and relevance. The questionnaire was then sent to 3650 staff within the 13 NHS trusts, seeking to achieve at least 600 responses as the basis for the factor analysis. 1307 questionnaires were returned (36% response). Factor analyses and reliability analyses were carried out on 897 responses from staff involved in direct patient care, to explore how consistently the questions measured the underlying constructs of safety climate and teamwork. Results: Some questionnaire items related to multiple factors or did not relate strongly to any factor. Five items were discarded. Two teamwork factors were derived from the remaining 11 teamwork items and three safety climate factors were derived from the remaining 11 safety items. Internal consistency reliabilities were satisfactory to good (Cronbach's alpha ⩾0.69 for all five factors). Conclusions: This is one of the few studies to undertake a detailed evaluation of a patient safety climate questionnaire in UK health care and possibly the first to do so in primary as well as secondary care. The results indicate that a 22 item version of this safety climate questionnaire is useable as a research instrument in both settings, but also demonstrates a more general need for thorough validation of safety climate questionnaires before widespread usage.